FACTORS INFLUENCING IMPULSIVE BUYING OF SKINCARE PRODUCTS ON MARKETPLACES AMONG YOUNG CUSTOMERS IN GROBOGAN REGENCY - Diah Ayu Kharismawati; winarsih (LPPM Universitas An Nuur, 2025)
Background: The increasing number of marketplace users, especially on platforms such as TikTok and Shopee, has triggered changes in consumer behavior, particularly among young customers. This phenomenon arises not merely due to the convenient accessibility to items, yet is further impacted through the role played through digital content creators and evolving social trends online, which affect both emotional and spiritual aspects of users. In Grobogan Regency, this trend is seen in the growing impulsive buying behavior in skincare product purchases among young customers. Purpose: The current investigation is conducted to investigate the effect of creator user generated content, product attractiveness, and social media flexing lifestyle on impulsive buying behavior in online skincare product purchases among young customers in Grobogan Regency. Method: A descriptive approach within a quantitative framework was applied in this study. The sampling method implemented was purposive sampling. involving 96 respondents aged 13–25 years who actively accessed marketplaces, particularly TikTok and Shopee. The data collection process was carried out through a structured questionnaire and subsequently analyzed with SPSS software, utilizing validity and reliability assessments, multiple linear regression analysis, and t-test procedures. Results: The findings indicated that every hypothesis put forward in this study was supported. Creator user generated content had a positive and significant influence on impulsive buying. Product attractiveness also positively and significantly influenced impulsive buying. Additionally, social media flexing lifestyle positively and significantly affected the tendency of consumers to make impulsive purchases. Conclusion: Creator user generated content, product attractiveness, and social media flexing lifestyle each positively and significantly impact impulsive buying behavior. of skincare products among young customers in Grobogan Regency. Suggestion: Future research is recommended to apply open-ended questionnaires or mixed methods to gain deeper insights into the reasons behind respondents' answers. In addition, it is recommended incorporating moderating variables such as emotional attachment or trust to enhance the understanding of how creator user generated content, product attractiveness, and social media flexing lifestyle influence impulsive buying behavior more comprehensively.